A structural model of teachers' work-family conflict and well-being : work-family conflict efficacy and religious coping as predictors - Zanariah Ismail (Institute of Education, International Islamic University Malaysia, 2011)
Work-family conflict in Malaysia increases dramatically in line with the country's economic growth. This area, however, lacks extensive research. In order to understand work-family conflict and well-being in Malaysia, the present study was designed based on Frone et al (1992) model of work-family interface. This study aimed to investigate the relationship between work-family conflict and well-being with two predictors; work-family conflict efficacy and religious coping. Specifically, this study examined the relationship between Work-family Conflict Efficacy (WFC efficacy), Religious Coping (RC), Work-Family Conflict (WFC) and Well-Being (WB). The main purpose was to estimate the relationships of WFC efficacy, RC, WFC and wellbeing of married female teachers in Malaysia. Second, the study sought to constructvalidate the instrument to assess WFC of married female teachers in Malaysia. The sample was selected amongst two hundred and forty five married female teachers from secondary schools in Hulu Langat district. Data was collected using self-report questionnaires measuring WFC, well-being, WFC efficacy and RC. The data were analyzed using the Structural Equation Modeling (SEM) and Confirmatory factor Analysis (CFA) procedures. The hypothesized model for WFC and WB was tested through structural equation modeling and the results revealed that the WFC efficacy indirectly influenced WB via WFC, showing that married female teachers with high work-family conflict efficacy demonstrated less conflict which led to increased wellbeing such as low distress and low dissatisfaction. Second, the results showed that religious coping had a direct and negative impact on well-being, meaning that teachers with high religious coping led to increased well-being such as low distress and low dissatisfaction. Next, the results revealed strong empirical support for the reciprocal relationship between teachers' WFC and well-being. Further discussion on the theoretical, methodological, practical and implications were also explained.